BrainLab Neurosurgery Award 196 IDH-1 Mutated Glioblastomas Have a Less Invasive Phenotype Than IDH-1 Wild Type Glioblastomas: A Diffusion Tensor Imaging Study. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Price, Stephen J.; Boonzaier, Natalie R.; Lupson, Victoria; Larkin, Timothy
Abstract: INTRODUCTION: IDH-1 mutated glioblastomas (GBMs) are associated with a better prognosis than glioblastomas with wild type IDH-1. Most explanations for this improved prognosis is due to these tumors responding better to therapy. Recent work has suggested they have a different behavior. Diffusion tensor imaging (DTI) is able to explore the invasive behavior of glioblastomas and can identify a number of invasive phenotypes. Approximately 20% are minimally invasive and they have improved survival. This study aims to look at differences in invasive behavior in preoperative GBMs with IDH-1 mutation status. METHODS: Patients with resectable glioblastomas were imaged at 3T with a protocol including DTI. The DTI data were decomposed into isotropic (p) and anisotropic (q) components and these abnormalities were outlined. The difference between these regions has been previously shown to be the region of invasion and was classified according to previously published classification. The tumors were resected and the IDH-1 status assessed using immunohistochemistry for the R132 mutation. RESULTS: Sixty-eight patients were studied—9 IDH-1 mutated GBMs, and 57 wild type IDH-1. All of the IDH-1 tumors exhibited minimally invasive DTI patterns. Only 5 (8%) of the IDH-1 negative tumors were minimally invasive, 14 (23%) were locally invasive and the majority, 41 (69%), had a diffuse pattern of invasion. All the IDH-1 group showed tumor surrounded by intact white matter. This was confirmed by measures of the diffusion tissue signature of adjacent white matter. CONCLUSION: We have shown that IDH-1 mutated GBM have a different invasive behavior compared to the non-mutated GBMs. This difference is seen at first presentation and is not related to response to therapy. This lack of invasion can help explain the better prognosis of this GBM subtype.